Neglecting Laws and Rights of Local Communities: A Human Rights-Based Approach Analysis of the Development of Indonesia’s New Capital City - Marzuki, Suparman; Heryansyah, Despan; Hadi, Sahid (Brawijaya Law Journal, 2024)
It is reported that the development of Nusantara as Indonesia’s new capital city tends to be pragmatic and disregards the quality of its processes and outcomes. Such a development has reduced the public’s trust, mainly because of this project’s environmental loss, social-humanity problems, and economic challenges. By employing human rights-based approaches to development, this article discusses the implementation and policy issues of the development of Nusantara in more depth and detail based on the rights holders’ experiences living in the Nusantara and its neighbouring areas. The research reveals that the development of Nusantara, ranging from its planning and policy formulation to its implementation, clearly neglected applicable laws and regulations. It failed to respect the rights of local communities, including indigenous peoples who enjoy their livelihoods in Nusantara and its neighbouring areas. We argue that the lack of respect and protection of human rights in the development implementation is because the development policy of Nusantara is grounded in autocratic legalism, even if it is established in a democratic mechanism.